(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
Rising Carbon Dioxide (CO2) levels and global warming concerns challenge the sustainability of fossil fuels as primary energy sources. Hydrogen is emerging as a crucial energy carrier, offering reduced carbon emissions and minimal harmful gases. Methods like hydrocarbon reforming and water electrolysis, especially when powered by renewable sources like wind and solar, enable hydrogen production. Hydrogen's purity and compatibility with fuel cells make it an eco-friendly alternative with high energy output. This project models a solar Photovoltaic(PV)-based hydrogen production system to address environmental concerns. Using MATLAB/Simulink for dynamic simulation, it accurately represents and analyses the hydrogen production for different regions which having different irradiances. Initial results highlight V-I and V-P curves for PV systems, revealing optimal conditions for efficient hydrogen production through electrolysis. This research advances sustainable hydrogen generation methods, emphasizing solar PV's potential to foster an eco-friendly and efficient energy landscape.